Reduced Glycemic Variability in Diazoxide-Responsive Children with Congenital Hyperinsulinism Using Supplemental Omega-3-Polyunsaturated Fatty Acids; A Pilot Trial with MaxEPAR - Skae, Mars; Avatapalle, Hima Bindu; Banerjee, Indraneel (Indi); Rigby, Lindsey; Vail, Andy; Foster, Peter; Charalambous, Christiana; Bowden, Louise; Padidela, Raja; Patel, Leena; Ehtisham, Sarah; Cosgrove, Karen E.; et al. (Frontiers in Endocrinology, 2014)
Objective: Congenital hyperinsulinism (CHI) is a rare condition of hypoglycemia where therapeutic options are limited and often complicated by side-effects. Omega-3-polyunsaturated fatty acids (PUFA), which can suppress cardiac myocyte electrical activity, may also reduce ion channel activity in insulin-secreting cells. PUFA supplements in combination with standard medical treatment may improve glucose profile and may reduce glycemic variability in diazoxide-responsive CHI. Design: Open label pilot trial with MaxEPAR liquid (eicosapentaenoic and docosahexaenoic acid) PUFA (3 ml/day for 21 days) in diazoxide-responsive CHI patients (https://eudract.ema.europa.eu/, EudraCT number 201100363333). Methods: Glucose levels were monitored pre-treatment, end of treatment, and at follow-up by subcutaneous continuous glucose monitoring systems (CGMS) in 13 patients (7 girls) who received PUFA. Outcome measures were an improved glucose profile, reduced glycemic variability quantified by a reduction in the frequency of glucose levels <4 and >10 mmol/l, and safety of PUFA. All children were analyzed either as intention to treat (n = 13) or as per protocol (n = 7). Results: Mean (%) CGMS glucose levels increased by 0.1 mmol/l (2%) in intention to treat and by 0.4 mmol/l (8%) in per protocol analysis (n = 7). The frequency of CGMS <4 mmol/l was significantly less at the end of treatment than in the pre-treatment period [556 (7%) vs. 749 (10%)]. Similarly, the frequency of CGMS >10 mmol/l, was also less at the end of treatment [27 (0.3%) vs. 49 (0.7%)]. Except for one child with increased LDL cholesterol, all safety parameters were normal. Conclusion: MaxEPAR was safe and reduced glycemic variability, but did not increase glucose profiles significantly in diazoxide-responsive CHI. The supplemental value of PUFA should be evaluated in a comprehensive clinical trial.